2016
DOI: 10.1021/acs.iecr.5b04427
|View full text |Cite
|
Sign up to set email alerts
|

High-Throughput Crystallization of l-Alanine Using iCrystal Plates and Metal-Assisted and Microwave-Accelerated Evaporative Crystallization

Abstract: We present a comprehensive study of highthroughput crystallization of L-alanine (a model amino acid) using circular crystallization platforms (are hereafter referred to as the iCrystal plates) designed to work with the metalassisted and microwave-accelerated evaporative crystallization (MA-MAEC) technique. The iCrystal plates are constructed using a circular 21-, 95-, and 204-well design that afford for homogeneous microwave heating of all samples. In addition, the iCrystal plates were modified with metal thin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 49 publications
(72 reference statements)
0
5
0
Order By: Relevance
“…In this regard, ITO films, which are developed for solar energy technology, are proven successful in all the criteria mentioned above. The Aslan Research Group have previously demonstrated the use of silver, gold, nickel and copper for rapid crystallization of amino acids in a recent publication [ 23 ].…”
Section: Resultsmentioning
confidence: 99%
“…In this regard, ITO films, which are developed for solar energy technology, are proven successful in all the criteria mentioned above. The Aslan Research Group have previously demonstrated the use of silver, gold, nickel and copper for rapid crystallization of amino acids in a recent publication [ 23 ].…”
Section: Resultsmentioning
confidence: 99%
“…5). 9 The longest crystallization time (i.e., when the complete evaporation of the solvent occurred) was observed on nickel-coated platforms with a time of ∼275 min at room temperature (Fig. 5).…”
Section: Simulation Of the Electric Field And Temperature Distributio...mentioning
confidence: 97%
“…The use of iCrystal plates with silver thin films at 50 °C along with microwave heating resulted in the growth of the largest number of L-alanine crystals (∼154 in 21-wells) and ranging in size between 59-625 μm as compared to all other experimental conditions. 9 The observed differences in the complete solvent evaporation time can be attributed to the differences in the thermal conductivities of the metal surfaces, which results in different rates of cooling of L-alanine solution.…”
Section: Simulation Of the Electric Field And Temperature Distributio...mentioning
confidence: 99%
See 1 more Smart Citation
“…The crux of the MA-MAEC technique is the generation of microwave-induced thermal gradients and the subsequent rapid mass transfer of biomolecules directed toward the metal nanostructures on planar surfaces that act as nucleation sites and microwave-transparent medium. Metal nanostructures of silver, gold, copper, nickel, and indium tin oxide are deposited onto poly­(methyl methacrylate) (PMMA) platforms combined with silicon isolators (i.e., the iCrystal plates). The unique design of the iCrystal plates ensures that microwave radiation is distributed homogeneously across the wells formed by the silicon isolator. , In studies based on the MA-MAEC technique by our research group to date, two different microwave systems operating at 2.45 GHz was employed: a multimode conventional microwave system (fixed power, 700–1000 W) , and the iCrystal system (monomode, variable power up to 100 W) . Conventional microwave system is a commercially available microwave oven that was initially used to demonstrate the proof-of-principle demonstration and applications of the MA-MAEC technique for the crystallization of biological compounds. The iCrystal microwave system is an instrument developed by our research group and was also employed for the crystallization of a variety of biomolecules …”
Section: Introductionmentioning
confidence: 99%